Nutritional composition of bilberries (Vaccinium myrtillus L.) from forest fields in Norway – Effects of geographic origin, climate, fertilization and soil properties - Rohloff, Jens; Uleberg, Eivind; Nes, Arnfinn; Krogstad, Tore; Nestby, Rolf; Martinussen, Inger (Julius Kühn-Institut - Bundesforschungsinstitut für Kulturpflanzen (Federal Research Centre for Cultivated Plants), 2015)
Effects of different environmental factors (origin, climate, fertilization and soil properties) on berry nutritional quality were studied in eight forest fields of bilberry (Vaccinium myrtillus) in Northern-, Mid- and Southern Norway. No clear trend between locations could be found, however untargeted multivariate analysis of metabolite profiles revealed clear segregation patterns between locations. Anthocyanin, and phenolics content, and titratable acidity were significantly affected by mineral fertilization (Mid-Norway), while organic fertilization did not show any significant effects (Northern Norway). Bilberry chemical composition was affected by harvest time point, as indicated by a potentially higher nutritional quality regarding the content of phytochemicals when harvesting at mid or towards the end of the production season (Southern Norway). Regional and annual climate had strongest impact on the nutritious content of bilberries. Significant differences were found between locations, however previous findings on increasing anthocyanin content with latitude were not confirmed due to environmental impacts confounding the population effects. publishedVersion Copyright (c) 2015 The Author(s). This work is licensed under a Creative Commons Attribution-ShareAlike 4.0 International License.